Timing of gain does not alter puberty and reproductive performance of beef heifers fed a high-roughage diet - Lynch, J.M.; Lamb, G.C.; Miller, B.L.; Minton, J. Ernest; Cochran, R.C.; Brandt, Robert T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty crossbred heifers (549 lb initial body weight) were developed in drylot and limit-fed a forage sorghum silage diet predicted to produce gains of either 1 lb/day for the entire developmental period (EVENGAIN) or .25 lb/day for the first two-thirds of the period followed by 2 lb/day during the last third (LATEGAIN). Treatments began on November 7, 1994 and continued until April 24, 1995 (onset of the breeding season). Actual daily gains over the entire feeding period averaged 1.18 and 1.10 lb/day for EVENGAIN and LATEGAIN heifers, respectively. Age and weight at puberty were not affected by feeding treatment. Body condition score, frame score, and pelvic area were similar at the end of the experiment regardless of growth regimen. At the conclusion of the 168-day feeding period, estrus was synchronized using two injections of prostaglandin F2", and heifers were inseminated artificially during a 45-day breeding season. Open heifers were mated naturally for an additional 15 days. First service and overall pregnancy rates were similar between treatments. In summary, timing of gain did not affect the onset of puberty or breeding performance. These data indicate that bee f producers may be able to utilize low quality feedstuffs early in heifer development without adversely affecting reproductive performance. Because feed inputs are major costs for developing beef heifers, such a management alternative may decrease costs.
Keywords: Beef; Heifers; Puberty; Heifer development; High-roughage diet